A. M. Samoilenko's numerical-analytic method without determining equation - Kovalenko, O. V.; Trofimchuk, E. P. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We suggest a modification of A. M. Samoilenko's numerical-analytic method for investigating the problem $dx/dt=f(t,x), \mathfrak{L}(x) = d$ (here $\mathfrak{L}(x): C([0, T], R^n) → R^n$is a linear continuous operator} in which it is not necessary to solve an additional determining equation.